Urban transformations and public health in the emergent city - Keith, M; De Souza Santos, A (Manchester University Press, 2020)
Urban transformations and public health in the emergent city examines how urban health and wellbeing are shaped by migration, mobility, racism, sanitation and gender. Adopting a global focus that spans Africa, Asia, Europe and Latin America, the essays in this volume bring together a wide selection of voices that explore the interface between social, medical and natural sciences. Moving beyond traditional approaches to urban research, this interdisciplinary approach offers a unique perspective on today's cities and the challenges they face.